2018
DOI: 10.18203/2320-1770.ijrcog20183327
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancy in women with previous one cesarean section

Abstract: Background: Worldwide rise in cesarean section (CS) rate during the last three decades has been the cause of alarm and needs an in-depth study. The purpose of this study was to determine the outcome of pregnancy in women with previous one cesarean section and maternal and perinatal complications. It also aimed at identifying the factors, which can influence the outcome of trial of labour (TOL).Methods: The prospective study was conducted in the department of Obstetrics and Gynaecology, Kamla Nehru hospital for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…152 participants were given a trial of labor among which 107(70.39 %) had successful VBAC and 45(29.61%) had repeat emergency C-sections. [17} As compared to this study our study showed a low VBAC percentage because all participants were not given a trial of labor [17]. In the Kingdom of Saudi Arabia, a retrospective Cohort study was conducted that was published in 2019 and had 299 women under study, 73.9% of the participants had successful vaginal births with no reports of any morbidity or mortality.…”
Section: Discussionmentioning
confidence: 58%
“…152 participants were given a trial of labor among which 107(70.39 %) had successful VBAC and 45(29.61%) had repeat emergency C-sections. [17} As compared to this study our study showed a low VBAC percentage because all participants were not given a trial of labor [17]. In the Kingdom of Saudi Arabia, a retrospective Cohort study was conducted that was published in 2019 and had 299 women under study, 73.9% of the participants had successful vaginal births with no reports of any morbidity or mortality.…”
Section: Discussionmentioning
confidence: 58%
“…Women with previous caesarean sections constitute a high risk group in obstetrics, because their pregnancy is associated with increased risk of maternal and fetal morbidity and mortality, during pregnancy, delivery and postpartum [2,3,4] . currently, women who will be allowed a VBAC must have fulfilled a certain criteria which included prior history of previous vaginal delivery with an average sized baby, women with interpregnancy interval of at least 15 months or inter-delivery interval of at least 24 months, non-recurrent indication in the previous delivery and no history of puerperal infection in the previous CS [2,3,6] .…”
Section: Discussionmentioning
confidence: 99%
“…The merits of vaginal birth following a caesarean abound: it affords the parturient the opportunity of self-fulfilment following a successful outcome, secondly it reduces the risks and morbidity associated with abdominal delivery-both anaesthetic risk and risk of surgery itselfthromboembolism, surgical site infection, increase cost of health care, less hospital stay. It therefore becomes imperative to assess the possibility of a vaginal birth following a previous caesarean delivery in pregnant women who meet the criteria [3,4] . This is even more important in low and middle income countries where greater premium is placed on large family size, and a sizeable percentage of the obstetrics population still have aversion for caesarean section [3,5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation